On some inequalities for derivatives of algebraic polynomials in unbounded regions with angles - Cevahir Doğanay Gün (MANAS: Journal of Engineering)
In this work we study Bernstein-Walsh-type estimations for the derivative of an arbitrary algebraic polynomial in regions with interior zero and exterior non zero angles.